2017
DOI: 10.3389/fmicb.2017.02524
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Characterization of SLA Class I Molecules Binding to Swine-Origin Viral Cytotoxic T Lymphocyte Epitope Peptides in Vitro

Abstract: Swine leukocyte antigen (SLA) class I molecules play a crucial role in generating specific cellular immune responses against viruses and other intracellular pathogens. They mainly bind and present antigens of intracellular origin to circulating MHC I-restricted cytotoxic T lymphocytes (CTLs). Binding of an appropriate epitope to an SLA class I molecule is the single most selective event in antigen presentation and the first step in the killing of infected cells by CD8+ CTLs. Moreover, the antigen epitopes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…The current study demonstrated that SLA-1 was a potential target gene of prv-miR-LLT11a by using RNAhybrid software based on the miRNAs and target gene's secondary structures; in addition, a dual luciferase assay method was utilized for verification of results. In previous study, SLA class 1 molecular (SLA-1) genes have been shown to have pivotal roles in specific cellular immune responses against viral infections [32]. Furthermore, it was reported that SLA-1-mediated antigen presentation pathways can be antagonized by PRV to evade the immune responses of the hosts [33].…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated that SLA-1 was a potential target gene of prv-miR-LLT11a by using RNAhybrid software based on the miRNAs and target gene's secondary structures; in addition, a dual luciferase assay method was utilized for verification of results. In previous study, SLA class 1 molecular (SLA-1) genes have been shown to have pivotal roles in specific cellular immune responses against viral infections [32]. Furthermore, it was reported that SLA-1-mediated antigen presentation pathways can be antagonized by PRV to evade the immune responses of the hosts [33].…”
Section: Discussionmentioning
confidence: 99%
“…To identify the T‐cell epitopes for E2 protein of CSFV with higher accuracy, we established the following strategy: (a) we mapped the promising epitopes using IEDB 2.19 methodology (Recommended) of IEDB Analysis Resource (Lundegaard et al, ; Nielsen et al, ) (http://tools.iedb.org/mhci/) for pig species, restricted to the Swine Leukocyte Antigen (SLA) alleles: SLA‐1*0101, SLA‐1*1101, SLA‐1*1301 SLA‐2*0101, SLA‐3*0101, SLA‐3*0602. The restriction for SLA haplotypes was based on two criteria: the alleles present in the swine breeds Large White and Landrace (Sorensen et al, ), both present in Cuban pig population (Rios et al, ), and the SLA alleles identified which specifically bind different CTL epitopes of CSFV (Gao et al, ). The cut‐off score was set to IEDB ≤1 to guarantee maximum epitope‐like properties (Table S2; Lundegaard et al, ; Nielsen et al, ), for the prediction of T‐cell epitopes other software such as SYFPEITHI or BIMAS were not used since in these programs, predictions for alleles from pig are not available; (b) a search for MHC‐I binding was also performed using NetMHC 4.0 Server.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that the arginine at position 156 (156 Arg ) is essential for peptide binding of SLA-1*04:01, and when 156 Arg was mutated to alanine, the peptides bound by the mutant SLA-1*04:01 (R156A) became significantly different from those bound by SLA-1*04:01 (30). Another previous study reported that SLA-1*13:01 is quite similar to SLA-1*04:01 but has different properties in presenting peptides (31). The lack of corresponding cell lines and monoclonal antibodies against SLA-I makes it challenging for us to use the current MS method to comprehensively and accurately determine their differences in peptide binding caused by micropolymorphism.…”
Section: Introductionmentioning
confidence: 97%